Corneal Parameters in Patients with Multiple Sclerosis: A Pilot Study - Kiliç, Soner; Gündogan, Medine (Klinische Monatsblätter für Augenheilkunde, 2021)
Objective To evaluate the corneal topographic parameter values measured with the Pentacam Scheimpflug system in patients with multiple sclerosis (MS).Methods A total of 108 eyes of 62 MS patients were studied. In addition to a complete examination of anterior and posterior segments, all patients were scanned using the Pentacam Scheimpflug camera. The diagnosis of MS was made according to the McDonald criteria. All MS patients were clinically assessed using the Multiple Sclerosis Severity Score (MSSS).Results The mean age was 38.89 ± 10.18 years (36.16 – 41.30) for MS patients and 40.94 ± 9.44 years (38.49 – 43.11) for the controls (p = 0.26). Only central corneal thickness (CCT) and corneal volume (CV) values were significantly lower in MS patients (p < 0.001). The other corneal parameters were not significantly different between the study eyes and control eyes (p > 0.05 for all). Pachymetric measurements at the corneal apex were 525.69 ± 29.35 (518.29 – 533.67) µm for the study eyes versus 563.13 ± 23.70 (562.13 – 576.36) µm for the control eyes. CV were 59.22 ± 4.11(58.18 – 60.20) mm3 for the study eyes versus 62.78 ± 3.09 (62.38 – 64.00) mm3 for the control eyes.Conclusion This is the first study that has reported lower CCT and CV measurements in MS patients than healthy subjects of a similar age. These results should be supported by further studies.
Keywords: multiple sclerosis; corneal thickness; corneal volume; Pentacam